Transcriptional profiling of long non-coding RNAs regulating fruit cracking in Punica granatum L. under bagging - Wang, Yuying; Zhao, Yujie; Wu, Yaqiong; Zhao, Xueqing; Hao, Zhaoxiang; Luo, Hua; Yuan, Zhaohe (Frontiers in Plant Science, 2022)
Fruit cracking tremendously damages the appearance of fruit, easily leads to pathogen invasion, greatly reduces the marketability and causes immense economic losses. The pivotal role of long non-coding RNAs (lncRNAs) in diverse biological processes has been confirmed, while the roles of lncRNAs underlying fruit cracking remain poorly understood. In this study, the incidence of fruit cracking was 7.26% under the bagging treatment, the control group was 38.11%, indicating that bagging considerably diminished the fruit cracking rate. LncRNA libraries for fruit cracking (FC), fruit non-cracking (FNC) and fruit non-cracking under bagging (FB) in pomegranate (Punica granatum L.) were performed and analysed via high-throughput transcriptome sequencing. A total of 3194 lncRNAs were obtained with a total length of 4898846 nt and an average length of 1533.77 nt in pomegranate. We identified 42 differentially expressed lncRNAs (DELs) and 137 differentially expressed mRNAs (DEGs) in FC vs FNC and 35 DELs and 160 DEGs in FB vs FC that formed co-expression networks respectively, suggesting that there are involved in phytohormone signaling pathway, lignin catabolic process, lipid transport/binding, cutin biosynthetic process and cell wall organization. We also found that 18 cis-acting DELs regulated 18 target genes, and 10 trans-acting DELs regulated 24 target genes in FC vs FNC, 23 DELs regulate 23 target genes for the cis-acting lncRNAs and 12 DELs regulated 36 target genes in FB vs FC, which provides an understanding for the regulation of the fruit cracking. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis results demonstrated that DELs participated in calcium ion binding, glycerophospholipid metabolism, flavonoid biosynthetic process, cell wall biogenesis, xyloglucan metabolic process, hormone signal transduction and starch and sucrose metabolism. Our findings provide new insights into the roles of lncRNAs in regulating the fruit cracking and lay the foundation for further improvement of pomegranate quality.